Effects of defoliation on photosynthesis, dry matter production and yield in Soybean (Bangladesh Journal of Botany, 2015)
Two pot experiments were conducted to assess the effect of various degree of defoliation on photosynthesis, dry matter production and yield in soybean. Defoliation significantly increased rate of photosynthesis and transpiration and leaf conductance of the soybean genotypes however, it decreased dry matter production and yield. DOI: http://dx.doi.org/10.3329/bjb.v43i3.21592 Bangladesh J. Bot. 43(3): 261-265, 2014 (December)